2014
DOI: 10.4314/ejhs.v24i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Use of upper-arm anthropometry as measure of body-composition and nutritional assessment in children and adolescents (6-20 years) of Assam, northeast India

Abstract: BACKGROUND: Upper-arm muscle area (UMA), upper-arm fat area (UFA), arm-fat index (AFI), upper-arm fat estimate (UFE) and upper-arm muscle estimate (UME) was introduced for the assessment of body-composition. This cross-sectional study assessed age-sex specific upper-arm composition and nutritional status among children and adolescents. METHODS: The present cross-sectional study was conducted among 1545 (770 boys; 775 girls) Sonowal Kacharis of Dibrugarh District, Assam, Northeast-India, using multi-stage strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
3
10
0
2
Order By: Relevance
“…[19] A significant number of other Indian and international study findings acquiesce with our study findings. [20212223] Table 3 shows the regularity in consumption of meals, breakfast, and type of diet followed by students and its results were in accordance to other diverse studies performed on nursing and undergraduate candidates. [1617] Previous study findings highlighted the point of overweight/obesity in association with breakfast-skipping habit.…”
Section: Discussionsupporting
confidence: 75%
“…[19] A significant number of other Indian and international study findings acquiesce with our study findings. [20212223] Table 3 shows the regularity in consumption of meals, breakfast, and type of diet followed by students and its results were in accordance to other diverse studies performed on nursing and undergraduate candidates. [1617] Previous study findings highlighted the point of overweight/obesity in association with breakfast-skipping habit.…”
Section: Discussionsupporting
confidence: 75%
“…Recently, it has been shown, in boys and girls aged 5–12 years, that the upper arm muscle area (U) and upper arm circumference (C) of boys was higher than that of girls except at 5, 7 and 11 years of age . This same tendency, but for M, was reported in children and adolescents 6–20 years old in India . It has also been reported that the upper arm fat area is significantly higher in girls than in boys; however, it has been shown that it decreases in children 5–7 years old and subsequently increases from 7 to 10 years old .…”
Section: Discussionmentioning
confidence: 78%
“…23 This same tendency, but for M, was reported in children and adolescents 6-20 years old in India. 24 It has also been reported that the upper arm fat area is significantly higher in girls than in boys 23,24 ; however, it has been shown that it decreases in children 5-7 years old and subsequently increases from 7 to 10 years old. 23 This latter trend was found in the control group of this study as a significant increase in the percentage of children in the 75-90 percentiles for upper arm fat area ( Figure S2, Supporting Information).…”
Section: Discussionmentioning
confidence: 96%
“…Diversos estudios han evaluado a la ATR y la CMB como medidas indirectas de la talla y el peso respectivamente, comprobando la alta correlación que presentan. Si bien la mayoría de estos estudios se han destinado a la estimación de peso y talla en adultos mayores en países desarrollados (3) , existen investigaciones que analizaron esta correlación en la población infantil en otros países (3)(4)(5)(6)(7)(8)(9)(10)(11) , pero en nuestro conocimiento no existen estudios que hayan analizado esta correlación en el rango etario de 2 a 19 años y en Argentina incluso no existen valores de referencia nacionales publicados de ATR. Cuando se dificulta obtener la medición de la talla o longitud reclinada se utiliza la medida de segmentos corporales que sirvan para correlacionar con la altura.…”
Section: Introductionunclassified
“…Esta medida, se modifica rápidamente por los cambios en la ingesta calórica y proteica de los sujetos, viéndose reflejado de igual o similar forma que en el peso corporal (15) . Se ha demostrado la asociación directa de enfermedades, los cambios bioquímicos, diagnóstico clínico y el estado nutricional con la composición de la parte superior del brazo (7) . Esta medición en relación a la edad tiene el propósito de poder diagnosticar y clasificar la desnutrición (14,(16)(17)(18) .…”
Section: Introductionunclassified